Motivation-Building to Continue Studies for Junior High School Students through Training and Campus Visit Facilitating a First-Hand Experience - Subekti, Adaninggar Septi; Lestariningsih, Fransisca Endang (Universitas Galuh, 2024)
This community service programme was conducted to raise awareness of the students of SMP Negeri 2 Purwosari Gunungkidul, the school partner, on the importance of pursuing higher education for their future. This programme was designed and conducted in response to the needs analysis suggesting that the students at the school had a low learning motivation and many of them did not have any plan to pursue education even to high school. The programme was conducted in the form of two consecutive motivation-building activities. The first was conducted in the form of a session with the school partner. The session aimed to provide a venue for the students to share their actual dreams and to make them realise that achieving those dreams was not an impossibility. The second activity was a campus visit where the students of SMPN 2 Purwosari visited Universitas Kristen Duta Wacana and joined fun learning sessions. It was aimed to give them a first-hand experience of the learning atmosphere at university so that they could be motivated to pursue their study even at the university level. They were also facilitated to realise the many scholarship opportunities available allowing them to study at university even if they came from financially struggling families. More such community service programmes should be conducted in other contexts bearing similar characteristics of students to allow for the younger generation to dream high and fight for it